THE EFFECT OF CELEBRITY ENDORSER ON CONSUMER REPURCHASE INTENTION THROUGH BRAND TRUST (STUDY ON SHOPEE CONSUMERS IN MALANG CITY) - Franziska Bunga Citra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2021)
Intense competition among companies and entrepreneurs prompted people to adopt the best strategy to obtain and retain their customers. Along with the rapid advancement of current technology in the business field, many people benefit themselves by working collaboratively with influential figures in social media, commonly referred to as celebrity endorsers. This research aimed to investigate the effect of celebrity endorsers on consumer repurchase intention through brand trust, specifically in the case of Shopee consumers in Malang City. By employing a descriptive quantitative method and using questionnaire results from 150 respondents to gather the primary data, this research attempted to test the four proposed hypotheses, which later showed that all hypotheses were accepted. H1 stated that the celebrity endorser variable (X) influences the brand trust variable (Z), H2 stated that the brand trust variable (Z) influences the repurchase intention variable (Y), H3 stated that celebrity endorser variable (X) influences the repurchase intention variable (Y), H4 stated that celebrity endorser variable (X) has an indirect effect on the repurchase intention variable (Y) through the brand trust variable (Z). This research concluded that the trustworthiness, services, expertise, and attractiveness of both the brand and the associated celebrity endorser significantly impact consumers' repurchase intention at Shopee.Keywords: celebrity endorser, brand trust, repurchase intention, Shopee